ANALISIS KESESUAIAN LAHAN UNTUK TANAMAN ALPUKAT DI NAGARI TAEH BUKIK, KECAMATAN PAYAKUMBUH, KABUPATEN LIMA PULUH KOTA - Riko Lidarti; Teguh Haria Aditia Putra; Amir, Yusnaweti (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
This research aims to analyze the suitability of land for avocado cultivation (Persea americana Mill.) in Nagari Taeh Bukik, Payakumbuh District, Limapuluh Kota Regency, West Sumatra. The evaluation was carried out using an integrative approach which included spatial, laboratory and biophysical analysis to determine the level of land suitability based on environmental parameters that influence the growth of avocado plants. The research area is at an altitude of 499.2–1,241.7 meters above sea level with annual rainfall of 2,000–2,500 mm and is dominated by podzolic, latosol and glei humus soil types. The research method included taking 13 soil samples for analysis of physical and chemical properties (texture, pH, organic C content, nitrogen, phosphorus, potassium, and cation exchange capacity). Spatial analysis was carried out using a Geographic Information System (GIS) based on Landsat and DEMNAS imagery with thematic map overlays including soil type, land cover, and slope slope. The results of the research show that 30.97% of the area is classified in the S2tc class (sufficiently suitable for temperature limitations), 18.77% is included in the S2wa class (sufficiently appropriate for limited rainfall), 30.55% is in the S3tc class (marginally in accordance with temperature limitations), and 19.70% of the area is classified as unsuitable (N) for avocado cultivation. The main limiting factors found were temperature >30°C, high rainfall, and soil acidity level (pH 5.0–6.0). As recommendations, several land management strategies are proposed, namely: (1) implementing a drainage and irrigation system in the S2wa area to overcome rainfall constraints, (2) using heat-resistant varieties and implementing a partial shade system in the S2tc and S3tc areas to reduce the impact of high temperatures, and (3) diverting unsuitable land (N) for conservation or cultivation of other adaptive plants. This study confirms that 80.3% of the Nagari Taeh Bukik area has considerable potential for the development of avocado plants with the implementation of appropriate management strategies. It is hoped that the results of this research can be a reference in planning sustainable land use, supporting spatial data-based agriculture, and increasing avocado production in the region.